Fetal heart pathology on postmortem 3‐T magnetic resonance imaging. (26th December 2013) - Sandaite, Inga; Dymarkowski, Steven; De Catte, Luc; Moerman, Philippe; Gewillig, Marc; Fedele, Luigi; Deprest, Jan; Claus, Filip
ABSTRACT Introduction Postmortem magnetic resonance imaging (pmMRI) is increasingly used in perinatology, typically as an alternative or complement to conventional necropsy for central nervous system anomalies. Overall, it provides reliable information on structural malformations but was shown to be of limited use in examining the fetal heart. Objective We aimed to assess the fetal heart on 3‐T pmMRI in a consecutive series of fetuses with structural congenital heart defects (CHD) and to determine diagnostic evaluation limits in case of CHD. Methods A single‐center database was retrospectively reviewed. Only fetuses having CHD of functional significance were included. Fetal cardiac anatomy was assessed on T2‐weighted 3D multiplanar reconstructed images acquired using isovolumetric voxel size (0.3–0.8 mm3), which allows to visualize cardiac structures in situ in multiple fetal body planes. Cardiac pathology was classified into complex and isolated CHD. On the basis of clinically relevant findings, pmMRI was considered either diagnostic or not diagnostic. Results A total of 24 fetuses were included in this study. The median gestational age was 22 weeks and 2 days (range 12w5d–34w6d). The median delay between delivery of the fetus and MR was 6 h and 30 min (range 1 h and 30 min–19 h). PmMRI was diagnostic for 12 out of 13 (92.3%) complex CHD and for 6 out of 11 (54.5%) isolated CHD. In case of valvular malformation, a tentative diagnosis was reached in 7/11 cases (64%) on the basis of indirect features. Conclusions Postmortem MRI is a valid diagnostic tool for CHD in fetuses beyond 16 weeks up to term. © 2013 John Wiley & Sons, Ltd.